KONSEP TASAWUF PERSPEKTIF NEO-SUFISME - Nur Rahmad Yahya Wijaya; Rasuki (Kariman: Jurnal Pendidikan Keislaman, 2022)
Some say that the essence of Sufism is in fana' (ecstasy, self-destruction before God) and kasyf (disclosure to God) because through both, ma'rifah (direct relationship with God) as the goal of Sufism occurs. Neo-Sufism, as a new Sufism movement, rejects or doubts the ecstatic-mystical-philosophical elements of classical Sufism, and therefore prefers elements of puritanism (its compatibility with Islamic orthodoxy) and changes its escapist character (escape from the world) to activism (positive attitude towards, and self-involvement in, the world). The aim of this study is to further examine the differences between the nature of classical Sufism and neo-Sufism and to further assess neo-Sufism. As a method, the answers found regarding the nature of (classical) Sufism are used as a benchmark for assessing neo-Sufism. On this basis, it was later discovered that neo-Sufism cannot be called Sufism. That was because of his denial or doubt about kasyf as the essence of Sufism, with which, the goals of Sufism, such as ma'rifah and other Sufism experiences (al-ahwa al-sufiyyah) occur. Without the experience of Sufism there can be no Sufism.